Change by Successful Projects - IT and Change Projects in Hungary - Deák, Csaba (Theory, Methodology, Practice – Review of Business and Management, 2005)
The article’s attempt is to answer the management and organizational questions arisen about Hungarian change projects. The objectives of my research* were to uncover special areas concerning change management and reengineering projects and to investigate the conscious, organizational change for improving performance in the Hungarian economic environment. An effective change project cannot be reached without an IT support, requiring the demands of the age, because it plays an important role either in analyzing preparations of decisions, or in the realization of the change. The development of informatics in Hungary shows some deficiency both in the aspect of quality and in reliability. The imperfect development of informatics ruins the effects of changing projects. In general, though it depends on the nature of the project and the kind of work you do; you might have to engage in a variety of tasks you haven’t tackled before, such as assembling a team to complete the project on time and on budget, mapping out a plan and monitoring your progress at key steps along the way, using appropriate planning tools such as project management software or wall charts and keeping your team motivated and on target. In the research special Hungarian characteristic features were emphasized and a methodology of process change projec was created regarding the domestic circumstances. New and original statements were made, which deal with the achievement of change, the role of information technology, objectives and results of change projects in Hungary.